Re-conceptualizing Teachers’ Narrative Inquiry as Professional Development - Paula R. Golombek; Karen E. Johnson (Profile: Issues in Teachers' Professional Development)
We offer a more nuanced characterization of teachers’ narrative inquiry as professional development (Johnson & Golombek, 2002) by grounding our definition of and empirical research on teachers’ narrative inquiry from a Vygotskian sociocultural theoretical perspective. Our goal is to reaffirm our belief in the educational value of teachers’ narrative inquiry as “systematic exploration that is conducted by teachers and for teachers through their own stories and language” (p. 6), while empirically documenting the crucial role of teacher educators in creating mediational spaces, dialogic interactions, and pedagogical tools for teachers’ narrative inquiry to flourish as professional development. It is also our goal to re-conceptualize teachers’ narrative inquiry as unbounded by time and place, and as a more fluid and emerging process.